Strategi Guru dalam Mengatasi Learning Loss Selama Pandemi Covid-19 pada Mata Pelajaran IPA - Fahmi Yahya; Indah Dwi Lestari; Syarif Fitriyanto (Indonesian Publication Center, 2022)
The Covid-19 pandemic forced an abrupt shift from face-to-face instruction to distance learning across nearly all levels of education in Indonesia. This transition gave rise to learning loss, a decline in students’ learning achievement and competence, which was particularly pronounced in Science (IPA) subjects due to their reliance on experiments, observation, and hands-on practical work. This study systematically reviews the strategies teachers employed to address learning loss in Science instruction during 2019-2021. A Systematic Literature Review (SLR) method was used, searching Google Scholar, Sinta, and ERIC with the keywords “teacher strategy”, “learning loss”, “science learning”, and “Covid-19 pandemic”. After applying inclusion and exclusion criteria, the selected articles were analyzed thematically. The findings show that teacher strategies can be grouped into five main themes: (1) the use of varied digital media and platforms, (2) simplification of an emergency curriculum, (3) strengthened communication and collaboration with parents, (4) remedial teaching and ongoing formative assessment, and (5) enhancing motivation through contextual, home-based simple project learning. The study recommends strengthening teachers’ digital competence along with school and government policy support for the sustainable implementation of these strategies.